Outsourcing justice and the emergence of consumer ombudsman regulatory framework in the United Kingdom - Omoola Olalekan, Sodiq; Mohamed, Nurah Sabahiah (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
This study aims to examine the phenomenon of outsourcing access to justice in the consumer goods and service industry. It is argued that one of the primary functions of any government is the provision of access to and delivery of justice. However, in the consumer goods sector, regulatory reforms have enabled the government to outsource this function to private ADR service providers or consumer ombudsman. The paper adopts doctrinal methodology through the analysis of consumer ombudsman regulations and annual reports of private ADR entities in the United Kingdom. The study finds that outsourcing justice to consumer ADR entities through appropriate legal framework is capable industry. It is argued that one of the primary functions of any government is the provision of access to and delivery of justice. However, in the consumer goods sector, regulatory reforms have enabled the government to outsource this function to private ADR service providers or consumer ombudsman. The paper adopts doctrinal methodology through the analysis of consumer ombudsman regulations and annual reports of private ADR entities in the United Kingdom. The study finds that outsourcing justice to consumer ADR entities through appropriate